ANALISIS NILAI TAMBAH PENGOLAHAN NIRA AREN DI DESA POOPO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW (Added Value Analysis of Palm Sap Processing in Poopo Vilage East Passi Sub District Bolaang Mongondow Regency) - Meichers M. Moonik; Sherly G. Jocom; Yolanda Pinky Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to analyze added value analysis of palm sap processing in Poopo Vilage East Passi Sub District Bolaang Mongondow Regency. The data used in this study are primary data and secondary data and then analyzed descriptively.The results showed that the added value in processing palm sap into palm sugar was Rp.39,875, while for processing captikus the added value was Rp.9.964. The added value ratio obtained in palm sugar processing is 59%, while the added value ratio obtained in captikus processing is 28%. In this study, although the added value of captikus processing is moderate, the people of Poopo village prefer to develop a captikus processing business compared to palm sugar processing. Due to the long process and in the future it will be very profitable for farmers, so farmers prefer to process captikus compared to processing palm sugar.